Identifikasi Perbedaan Morfologi Alga Merah Bali (Gracilaria sp.) antara Bulung Gongseng dan Bulung Sangu - I Kadek Aryawan; I Gede Putu Wirawan; I Ketut Suada (Nandur, 2024)
Gracilaria sp. is a type of seaweed that grows in Indonesia, especially in the sea of Bali. There are two species of Gracilaria sp. known by the people of Bali, namely bulung gongseng and bulung sangu. The two species are morphologically similar. This research aims to identify the morphological differences between bulung gongseng and bulung sangu sangu taken from the sea of Tanjung Benoa. Observations were made on physical characteristics such as shape, length, thickness, surface texture, and thallus color of the bulung gongseng and bulung sangu which were then compared to each other, where observations on the surface of the thallus used a 24x magnification microscope. The results showed differences in morphology between the bulung gongseng and bulung sangu, including the thickness of the thallus of the bulung gongseng which was thicker, the lighter color of the bulung gongseng compared to the bulung sangu, and the nodule surface of the bulung gongseng compared to the smooth surface of the bulung sangu.